Bacterially Converted Oat Active Ingredients Enhances Antioxidative and Anti-UVB Photoaging Activities - Jennifer K. Lee; Inyoung Kim; Eun-Kyeong Jeon; Jung-Heun Ha; Cher-Won Hwang; Kim, Jin-Chul; Woong-Suk Yang; Hyunju Choi; Hee-Do Kim; Cheorl-Ho Kim (Oxford University Press, 2022)
Oat (Avena sativa L.) is one of the most widely consumed cereal grains worldwide and is considered as an important cereal crop with high nutritional value and potential health benefits. With different bacterial strains, fermented oat extracts were examined for the antioxidant and antiaging effects on the skin after optimization of extraction conditions. Fermented oats contained high avenanthramides, and its function was investigated on matrix metalloproteinase-1 and collagen expression with human dermal fibroblast cells. After fractionation, butanol layers showed the highest avenanthramides contents. Therefore, the microbial fermentation of oats enhances the quality and content of functional ingredients of oats, which provide natural dietary supplements, antioxidants, and antiaging agents.